Trading places. (Economist, 1998)
The New York Stock Exchange (NYSE) is talking of moving to New Jersey in order to provide more space for the 4,000 brokers and specialists who crowd its trading floor, despite the fact that exchanges everywhere are abandoning floor trading in favor of electronic dealing. The NYSE believes that it is its unique market structure, which centers on “specialists” who ensure that any would-be buyer or seller of a particular stock can find someone to trade with at all times, that has contributed to its huge success. The main threats to the NYSE, in terms of changes to the regulatory environment and the development of electronic trading, are discussed.